IMPLEMENTASI PENDIDIKAN KARAKTER DI SMP ISLAM TERPADU SITI HAJAR MEDAN - Robin Sirait (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2017)
Abstrak: This research used qualitative approach in terms of naturalistic. It was conductedtSMP IT Siti Hajar Medan. The source of this research was data and documents. The data wascollected through observation, interview and document analysis. The data used data reductiontechnique, data presentation and conclusion in the school environment and in the classrooms.Subjects of this research were headmaster, teachers, students, parents and students.The object of research was the implementation of character building which stated as the superiorschool programme, rules, condition of school, extra-curricular and intra-curricular activities.The instrument of research was interview guidance, observation sheets and field notes.The data was analysed withh qualitative descriptive method.Penelitian ini bertujuan untuk (1) mengetahui implementasi pendidikan karakter di SMP IslamTerpadu Siti Hajar Medan (2) mengetahui peran kepala sekolah, guru dan orang tuadalam pendidikan karakter siswa (3) mengetahui faktor-faktor yang mempengaruhi programimplementasi pendidikan karakter (4) hasil dari implementasi pendidikan karakter.Penelitianini menggunakan